Hannah Arendt and the search for a new political Philosophy - Parekh, Bhikhu (London, 1981)
Hannah Armd (1906-1975) was one of the mon stimulating political philosophers of the twentieth century. She has several daims to distinction. First, she is one of the few major political philosophers to philosophie systematically about politics again the background of Nazi sotalitarianium, one of the most important eves of our commary. She saw it at close quarters, suffered an is hands and never orased to wonder how it could happen. Second, she is the only political philosopher in history to take on the entire tradition of political philosophy and commend that it is "inauthomic and not really a tradition of polical philosophy at all Third, Armd is the first major political thinker in the English-speaking world to apply the phenomenological method to the understanding of politics The muthed has produced rick results in the fulds of this, songs, pychologs. anchutics, amidragulings and epistemology, but has so far not been applied so the study of politics Arena's work reveals back the wrongth and the weakness of the method. Fourth, Arendi in almost alone in the history of political philosophy, Uske Pine who sumedis under the caspory of orch, and unik Ar Aquines, Hottes, Locks, Bentham, Mill, Hegal and others who shoumed it under the category of the good which they all, no dows, defined very differently, Arend submes politics under bety. For her i is primarily concerned to make the world beautiful Fifth, she is a powerful advocate of a new culture based on a public way of life. Drawing on the experiences of classical Athens and Rome, she develops a novel vision of human life and articulates it in terms of such original and suggestive concepts as space of appearance, public space, public freedom and public happiness.
Keywords: Political science